Development of Chemical Physics Practicum Module Contextual Learning for Prospective Chemistry Teachers - Wijayanti, Imas Eva; Aisyah, Ratna Sari Siti; Andini, Andini; Paridah, Ida; Khoirunnisa, Khoirunnisa; Sutihat, Sutihat (EduChemia: Jurnal Kimia dan Pendidikan, 2023)
Learning chemistry requires practicum which functions to enrich understanding of chemical materials. Practical practice should ideally be carried out in a laboratory as a representative place to produce accurate and precise data using validated practical instructions. This study aims to create a chemistry practicum guide that is designed to be carried out at home with facilities around the house so that it can function to train student independence. This research is a product development research in the form of using model Analyze, Design, Develop, Implement, and Evaluate (ADDIE). The resulting product was validated by 6 material and media expert validators and then tested limited to 15 chemistry teacher candidate students. The results showed that the practicum instructions obtained an Aikens score of 0.9 from the validator, which means they are valid and feasible to try out. Then after conducting trials and student responses, a response of 86% was obtained in the very good category. Based on the values from the validator and limited trials, these practical instructions can be used by prospective Chemistry teachers in teaching in the classroom and at home.